Comparative Study of Conventional and Microwave Assisted Synthesis of Chalcones - Sharma, Bhavana (Asian Journal of Chemistry, 2011)
An efficient, facile and eco-friendly microwave assisted approach for the synthesis of substituted chalcones by condensation of substituted acetophenones with substituted benzaldehyds in presence of an inorganic base is desired over time consuming convention synthesis method. The reaction time brought down from hours to seconds along with yield enhancement of substituted chalcones. The structures of synthesized chalcones have been established on the basis of their spectral data.